Landmark essays on speech and writing - Elbow, Peter (New York Routledge, 2015)
"Classical rhetoric was originally all about speech; then it took an interest in writing. We are at a kind of mirror moment now. The present field of "composition and rhetoric" has been preoccupied with writing for the last fifty or more years, but finally people are looking again at speech and how it relates to writing. At this moment, then, when we are inheritors of research showing that writing can be thought of as different and yet not different from speech. In this volume, leading speech and writing expert, Peter Elbow, gathers a selection of classic essays that show the main streams of thinking that have gone on about speech and writing. Through the interdisciplinary essays included, he invites readers to think critically about the relationship between speech, writing, and our notion of literacy"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Rhetoric; Written communication